127 PENGARUH BRAND AMBASSADOR DAN KOREAN WAVE TERHADAP KEPUTUSAN PEMBELIAN PRODUK NATURE REPUBLIC PADA MASYARAKAT KOTA GRESIK - Tsany Diana Assyifa; Awin Mulyati; Sri Andayani (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2024)
The Korean wave has been spreading more and more over the last few years. The term "Korean Wave" refers to a number of South Korean products that are currently popular in Indonesia, including K-dramas, films, music (K-pop), fashion, food and cosmetics. K-Pop is currently quite popular among Indonesians of all ages, from teenagers to adults, women and men. The Korean Wave became widely adopted in Indonesia thanks in large part to K- pop. This study aims to ascertain how much influence Brand ambassadors and Korean Wave have on purchasing decisions for Nature Republic products in Gresik City Communities. To collect data, this research used a Google Form based questionnaire which was used as an instrument. The research sample consisted of 100 respondents. From the results of this t test, it shows that partially there is a positive and significant influence between the Brand Ambassador and Korean Wave variables on purchasing decisions for Nature Republic products for the people of Gresik City. As for the simultaneous f test, both also have a significant effect on the Purchase Decision of Nature Republic products in Gresik City Communities.